Creativity and Mirror Effect: Teaching Creative Skills Through Non-traditional Pedagogies - Alejandra Amenábar Álamos (DIID, 2024)
Design pedagogy is crucial for transferring project methodologies and fostering creative skills. However, the technological and social transformations of this century have challenged traditional educational canons and the very definition of creativity. This article proposes that this challenge can be analyzed through non-traditional educational paradigms to address this challenge from a design methodology perspective. It first reviews the existing literature on creativity training and presents a case study on training methodologies. This case was incorporated into an undergraduate design course, providing insight into design pedagogy itself. Then, the article discusses the future challenges and projections of Design education and the cultivation of creative skills for the 21st century. Finally, by examining alternative educational approaches, this research contributes to the current discourse on design pedagogy and its adaptation to the changing needs of contemporary society.